2019
DOI: 10.1371/journal.pone.0214079
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the protective capacity of mangroves from storm surges in coastal Bangladesh

Abstract: Mangroves are an important ecosystem-based protection against cyclonic storm surge. As the surge moves through the mangrove forest, the tree roots, trunks, and leaves obstruct the flow of water. Damage to adjacent coastal lands is attenuated mainly by reducing (i) surge height, which determines the area and depth of inundation and (ii) water flow velocity. But the extent of mangrove protection depends on the density of tree plantings and the diameter of trunks and roots, along with an array of other forest cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 42 publications
1
46
0
Order By: Relevance
“…Damage resistance in mangrove species conditions can produce velocities around 0.5-0.7 m s À1 (Fig. 7; Roeber and Bricker 2015;Dasgupta et al 2019). Despite the low flow conditions, the tests are still informative about the drag coefficient, which is known to be reasonably constant when the Reynolds number is above 1000 (2500 in our test; Hu et al 2014;Chen et al 2018).…”
Section: Drag Properties Of Mangrove Branchesmentioning
confidence: 81%
“…Damage resistance in mangrove species conditions can produce velocities around 0.5-0.7 m s À1 (Fig. 7; Roeber and Bricker 2015;Dasgupta et al 2019). Despite the low flow conditions, the tests are still informative about the drag coefficient, which is known to be reasonably constant when the Reynolds number is above 1000 (2500 in our test; Hu et al 2014;Chen et al 2018).…”
Section: Drag Properties Of Mangrove Branchesmentioning
confidence: 81%
“…A study for the United Kingdom showed that fronting protective structures with coastal wetlands significantly lowered seawall requirements and resulted in subsequent savings in construction costs (Mangi et al, 2011). Such a combination of "green" and "gray" infrastructure may be the most effective way of protecting vulnerable coasts from the variability of sea level rise, increased frequency and intensity of storms, and the risks of climate change (Mangi et al, 2011;Arkema et al, 2013;Barbier, 2014;Sandilyan and Kathiresan, 2015;World Bank, 2016;Dasgupta et al, 2019;Liu et al, 2019).…”
Section: Economic Valuation Methodsmentioning
confidence: 99%
“…Equally, the strength and duration of the storm, and the presence of high or low tides, can impact wave attenuation by ECEs significantly (Koch et al, 2009;Loder et al, 2009;Wamsley et al, 2010;Barbier et al, 2011). Only recently are valuation studies taking into account spatial and temporal variability of wave attenuation by ECEs in estimating their potential protective value (Barbier et al, 2008;Barbier, 2012;Dasgupta et al, 2019;Hochard et al, 2019).…”
Section: Spatial Variabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21][22]. Mangroves provide (a) resources such as food, timber and fuel [4][5][6][7]; (b) shoreline protection [8][9][10]; (c) refuge and habitat for marine and coastal species in several life stages [11][12][13]; and (d) recreation and tourism opportunities [14][15][16]. Notwithstanding the importance of mangroves, they continue to be threatened by natural and anthropogenic pressures.…”
Section: Introductionmentioning
confidence: 99%